Validating atlas-based lesion disconnectomics in multiple sclerosis: A retrospective multi-centric study - Ravano, Veronica; Andelova, Michaela; Fartaria, Mário João; Mahdi, Mazen Fouad A-Wali; Maréchal, Bénédicte; Meuli, Reto; Uher, Tomas; Krasensky, Jan; Vaneckova, Manuela; Horakova, Dana; Kober, Tobias; Richiardi, Jonas (NeuroImage. Clinical, 2021)
The translational potential of MR-based connectivity modelling is limited by the need for advanced diffusion imaging, which is not part of clinical protocols for many diseases. In addition, where diffusion data is available, brain connectivity analyses rely on tractography algorithms which imply two major limitations. First, tracking algorithms are known to be sensitive to the presence of white matter lesions and therefore leading to interpretation pitfalls and poor inter-subject comparability in clinical applications such as multiple sclerosis. Second, tractography quality is highly dependent on the acquisition parameters of diffusion sequences, leading to a trade-off between acquisition time and tractography precision. Here, we propose an atlas-based approach to study the interplay between structural disconnectivity and lesions without requiring individual diffusion imaging. In a multi-centric setting involving three distinct multiple sclerosis datasets (containing both 1.5 T and 3 T data), we compare our atlas-based structural disconnectome computation pipeline to disconnectomes extracted from individual tractography and explore its clinical utility for reducing the gap between radiological findings and clinical symptoms in multiple sclerosis. Results using topological graph properties showed that overall, our atlas-based disconnectomes were suitable approximations of individual disconnectomes from diffusion imaging. Small-worldness was found to decrease for larger total lesion volumes thereby suggesting a loss of efficiency in brain connectivity of MS patients. Finally, the global efficiency of the created brain graph, combined with total lesion volume, allowed to stratify patients into subgroups with different clinical scores in all three cohorts.
Keywords: lidé; Diffusion Tensor Imaging; mozek; Algorithms; retrospektivní studie; Brain; Humans; Retrospective Studies; roztroušená skleróza; Multiple Sclerosis; algoritmy; zobrazování difuzních tenzorů